Glass Microsphere‐Supported Giant Vesicles for the Observation of Self‐Reproduction of Lipid Boundaries. (5th December 2017) - Fiore, Michele; Maniti, Ofelia; Girard‐Egrot, Agnes; Monnard, Pierre‐Alain; Strazewski, Peter
Abstract: Growth and division experiments on phospholipid boundaries were carried out using glass microsphere‐supported phospholipid (DOPC) giant vesicles (GVs) fed with a fatty acid solution (oleic acid) at two distinct feeding rates. Both fast and slow feeding methods produced daughter GVs. Under slow feeding conditions the membrane growth process (evagination, buds, filaments) was observed in detail by fluorescence microscopy. The density difference between supported mother vesicles and newly formed daughter vesicles allowed their easy separation. Mass spectrometric analysis of the resulting mother and daughter GVs showed that the composition of both vesicle types was a mixture of original supported phospholipids and added fatty acids reflecting the total composition of amphiphiles after the feeding process. Thus, self‐reproduction of phospholipid vesicles can take place under preservation of the lipid composition but different aggregate size.